Using Guided Inquiry-Based Electronic Science Worksheets Assisted by Virtual Laboratories on the Science Process Skills of Middle School Students - C. Morokuhi, Yulina; K. Walanda, Daud; Santoso, Tri; Ningsih, Purnama; Aminah, Siti (Jurnal Pendidikan Indonesia, 2025)
The development of information and communication technology affects education. However, the limitation of interactive media is one of the obstacles in improving 21st century skills. This research aims to produce hyperdocs-based teaching modules in PjBL learning that are valid, practical and effective for improving creative thinking skills and collaboration skills of high school students. The type of research is R&D using the ADDIE model. The research subjects were class X students totaling 30 people. Data analysis used paired T-test with SPSS application. The instruments used were validation sheets, essay questions to measure creative thinking skills and observation sheets to measure collaboration skills. The results showed that the teaching module was feasible with a validity level of 77.91% (valid), practicality by teachers 97.22% (very practical), practicality by students 88.43% (very practical), and effectiveness 1,174 (large effect). Module implementation improved creative thinking skills with a value of 3.69, group collaboration skills with a value of 11.733, individual collaboration skills of 1.985 all in the large effect category. The results indicate that hyperdocs-based teaching modules can improve students' creative thinking and collaboration skills.